MENINGKATKAN PEMAHAMAN JENIS-JENIS USAHA DALAM MASYARAKAT PADA MATA PELAJARAN IPS MELALUI MODEL INTERAKSI EDUKATIF DI KELAS V SD NEGERI 006 PAGARAN TAPAH DARUSSALAM - Wijiyati ' (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2016)
This research is motivated by the poor results of social studies class V students of SD Negeri006 Pagaran Tapah Darussalam Rokan Hulu. This study aimed to determine the educationalinteraction model approach in improving the understanding of business in society (fishing) insocial studies in class V SD Negeri 006 Pagaran Tapah Darussalam, held for 1 month.Subjects in this study were all students of class V SD Negeri 006 Pagaran Tapah Darussalam,the number of students by 22 students with academic ability heterogeneous. Form of researchis classroom action research. The research instrument consists of instruments and instrumentperformance data collection activity observation sheet form teacher and student activity.Based on the analysis and discussion can be concluded that the average student learningoutcomes in initial tests is average with the average value of 59.55, and in the first cycle roseto 69.32 in the medium category, while in the second cycle of average ability studentscategorized as high in percentage the average value of 87.05 by the very high category. Fromthe above data it is known that there is a close link between the increased activity of teachersand students with student success in learning. The statement indicates that results for studentswith understanding the material efforts within the community learning model InteractionEducational fifth grade students of SD Negeri 006 Pagaran Tapah Darussalam can beenhanced through learning model Interaction Educational.